2001
DOI: 10.1093/ajcn/74.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Use of biological markers to validate self-reported dietary intake in a random sample of the European Prospective Investigation into Cancer United Kingdom Norfolk cohort

Abstract: These data indicate that, despite increased subject burden, the 7-d food diary provided a better estimate of nitrogen and potassium intakes than did the FFQ in this study population. However, with respect to plasma ascorbic acid, both the FFQ and 7-d food diary provided a similar ranking of subjects according to vitamin C intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
154
4
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 39 publications
12
154
4
7
Order By: Relevance
“…The consistency of the 7DD, HLQ and FFQ in the present analysis of alcohol and risk of CHD is aligned with the results of previous validation studies, in which good agreement was found among self-reported instruments (26)(27)(28)(29)(30)(31) . Some of the correlation between self-reported instruments may be attributable to within-person error (32) .…”
Section: Discussionsupporting
confidence: 88%
“…The consistency of the 7DD, HLQ and FFQ in the present analysis of alcohol and risk of CHD is aligned with the results of previous validation studies, in which good agreement was found among self-reported instruments (26)(27)(28)(29)(30)(31) . Some of the correlation between self-reported instruments may be attributable to within-person error (32) .…”
Section: Discussionsupporting
confidence: 88%
“…This observation corresponds to several urinary nitrogen biomarker studies (Rothenberg et al, 1993;Rothenberg, 1994;Bingham and Day, 1997;Bingham et al, , 2001Klipstein-Grobusch et al, 1998;Day et al, 2001;McKeown et al, 2001;Mahabir et al, 2006) and a pooled analysis of fibre and colorectal cancer (Dahm et al, 2010). However, evidence that 7DD and the FFQ estimates of alcohol were similarly associated with CHD, suggesting that such differences may be specific to specific nutrients rather than existing instrument-wide (Ward et al, 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Biomarker validation studies have yielded evidence of more accurate reporting of total energy (Mahabir et al, 2006), protein and potassium (Rothenberg et al, 1993;Rothenberg, 1994;Bingham and Day, 1997;Bingham et al, , 2001Klipstein-Grobusch et al, 1998;Day et al, 2001;McKeown et al, 2001) in the DD relative to the FFQ, though this is not a universal observation (Scagliusi et al, 2008). In the absence of biomarkers, the relative accuracy of dietary assessment methods can be assessed by comparing diet-disease associations ascertained from different instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐report measure of fruit and vegetables consumption consisted of a validated questionnaire FFQ (McKeown et al ., 2001) calculated as a delta change score between participants' measures obtained at baseline and at follow‐up. This study did not use an objective measure of consumption of fruit and vegetables.…”
Section: Methodsmentioning
confidence: 99%